Improving the performance of throws in freestyle wrestling using electrical muscle stimulation - Podlivaev, B. A.; Rozhin, N. N.; Yakovlev, B. A. (International Journal of Wrestling Science, 2014)
The relevance of this work is due to the fact that despite the numerous studies of the sporting and technical skills of wrestlers, little attention has been paid to the study and justification of new pedagogical tools and methods for achieving sporting perfection in wrestling. The issue of sporting perfection in wrestling has become of particular importance in recent years due to the large number of young athletes with very good performances at youth and junior competitions who do not go on to become top adult athletes. One of the reasons for this is that the training tools and methods are developed without considering the potential ability of young wrestlers. This often stops them from continuing their successful wrestling training when moved into a group of adult athletes. The trainer has virtually no tools or methods for looking into the future of their students. In addition, sports science has developed control techniques that can be used to intensify the process of performing training exercises, so that this process approaches a high level of sport performance (I.P. Ratov 1972, V.A. Khvilon, 1974). The possibility of doing this, even on an artificial basis, makes it possible to evaluate the sporting future of a young wrestler.